Kemiskinan Dan Faktor Penyebabnya di Kelurahan Deringo Kecamatan Citangkil Kota Cilegon - Restu Nur Aisah; Aris Supriyo Wibowo; Andjar Astuti; Suherman Suherman (JURNAL AGRIBISNIS TERPADU, 2020)
Poverty is a common problem in Indonesia. One of them is in Dringo Sub District, Citangkil District, Cilegon City, which has increased the number of target housholds over the past five years. This research was conducted in Dringo Sub District, Citangkil District, Cilegon City from May to October 2019. The purpose of this research is to identify the cause of poverty and analyze poverty levels based on the size of the severity index and the poverty index. Primary and secondary data was used I this research. The detailed analysis is used to identify the cause of poverty, and the level of poverty is measured by the index number, the poverty index and the poverty severity index. The results showed that there were 5 factors causing poverty, namely education level, employment opportunity, number of family members in the responsibility, access to health, and access to water and sanitation. Of the five factors of education and employment opportunity to be the most dominant factor. The index of poverty was 0.21 and the indkes of poverty was 0.11. This shows that the average cost of the household is closer to the poverty line compared to the overall expenditure of the poor in Cilegon, but the inequality of households is lower than the inequality of poor population expenditure in Cilegon.